Production of hand music videos in anatomy education for medical students in Malaysia - Abas, Razif; Minhat, Halimatus Sakdiah; Zakariah, Siti Zulaikha; Ibrahim, Rosni; Mohamed Razali, Camellia Siti Maya; Salleh, Marzelan (Penerbit Universiti Sains Malaysia, 2023)
Media are teaching resources that help teachers transmit messages and learning material to students effectively and efficiently. Music video making is one example of how educational media is used in anatomy training. The aim of this article is to elaborate the stages of hand music video development. The three main stages of film and video production are pre-production, production, and postproduction. Identifying the type of music video, script writing, song composition, music and vocal recording, and storyboard production are all parts of the pre-production stage. Shooting and selecting the music video’s mood, with a few adjustments, are part of the production stage. Finally, editing is included in the post-production stage. Hand music videos were found to aid in the teaching of anatomy, with the music video containing visual, auditory, and kinaesthetic elements. Therefore, music videos can be used as an alternative teaching approach, particularly in difficult subject areas that demand extensive memorisation.